2000
DOI: 10.1128/mcb.20.21.7955-7970.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Splice Site Pairing via Intron Definition in Schizosaccharomyces pombe

Abstract: Schizosaccharomyces pombe pre-mRNAs are generally multi-intronic and share certain features with premRNAs from Drosophila melanogaster, in which initial splice site pairing can occur via either exon or intron definition. Here, we present three lines of evidence suggesting that, despite these similarities, fission yeast splicing is most likely restricted to intron definition. First, mutating either or both splice sites flanking an internal exon in the S. pombe cdc2 gene produced almost exclusively intron retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 74 publications
12
70
2
Order By: Relevance
“…This effect was reproducible, and was not observed upon mutating the 5Ј-splice site alone. Thus, these results raise the possibility that there may be communication across exon 6 in the srp2 pre-mRNA; this is contrary to our earlier proposal that exon definition does not occur in S. pombe, based on our inability to induce skipping by mutating the splice sites flanking exons that lack purine-rich sequences (Romfo et al 2000).…”
Section: Mutating the Srp2 Element Does Not Have A Dramatic Effect Incontrasting
confidence: 55%
See 3 more Smart Citations
“…This effect was reproducible, and was not observed upon mutating the 5Ј-splice site alone. Thus, these results raise the possibility that there may be communication across exon 6 in the srp2 pre-mRNA; this is contrary to our earlier proposal that exon definition does not occur in S. pombe, based on our inability to induce skipping by mutating the splice sites flanking exons that lack purine-rich sequences (Romfo et al 2000).…”
Section: Mutating the Srp2 Element Does Not Have A Dramatic Effect Incontrasting
confidence: 55%
“…Our finding that the SRP2 element, which is found downstream from two micro-exons, functions as a splicing enhancer, combined with our previous demonstration that such pre-mRNAs are inherently inefficient splicing substrates in S. pombe (Romfo et al 2000), suggested a strategy for identifying additional native splicing enhancers. Based on the hypothesis that ESEs may have evolved and been maintained to ensure the splicing of such pre-mRNAs, we examined a subset of the ∼2.5% of S. pombe genes that contain internal micro-exons for downstream purine-rich motifs.…”
Section: S Pombe Gar-type Sequences Downstream From Micro-exons Thatmentioning
confidence: 98%
See 2 more Smart Citations
“…In this report, we present evidence that U1 snRNA is a key trans-acting factor in the activation of an unusual cryptic 59 splice site in the second intron of the cdc2 gene from S. pombe+ In experiments described elsewhere, we have altered the distance between the cryptic 59 junction and the other splicing signals within this intron )+ The results demonstrate that moving the cryptic 59 splice site farther away from the 39 splicing signals dramatically diminished its use, indicating that proximity to the branchpoint is critical for its activation+ Conversely, decreasing the size of the intron allowed the natural 59 splice site to compete much more effectively with the cryptic 59 junction+ These findings are consistent with the prevalence of extremely small introns in S. pombe (Zhang & Marr, 1994;Romfo et al+, 2000)+ An important goal of future work will be to uncover the factor(s) that collaborate with U1 to impose the distance constraints on splice site pairing in S. pombe+ FIGURE 4. A: Potential base pairing of mutant U1 snRNAs to the cryptic 59 splice site+ The aberrant nucleotide within the cryptic junction and the nucleotide mutated in each U1 allele are shown in white against a black background+ The percentage of product corresponding to mRNA spliced at the cryptic junction is taken from the experiment shown in Figure 3B+ B: Effects of two U1 alleles that pair to different extents with the cryptic 59 splice site on the profile of products from cdc2-Int2 mutants+ The experimental design was as in Figure 3+ Because the vast majority of 59 splice sites from diverse species, whether natural or cryptic, contain a U as the second nucleotide (Newman & Norman, 1991;Krawczak et al+, 1992;Kandels-Lewis & Séraphin, 1993;Lesser & Guthrie, 1993;Crispino & Sharp, 1995;Burge et al+, 1999;Spingola et al+, 1999), the presence of an A at position ϩ2 of the cryptic 59 junction in S. pombe cdc2 is unusual+ However, it is not unprecedented, as both a developmentally regulated alternative 59 splice site in the terminal intron of Drosophila melanogaster Antp (Bermingham & Scott, 1988) and a cryptic 59 splice site in mammalian ras (Cohen et al+, 1994) share this anomaly+ How do these 59 junctions circumvent the normal sequence requirements for splicing?…”
Section: Discussionsupporting
confidence: 78%